Experimental study on the effect of a heated plume within vented enclosures - Tiong, Ing Kee (Curtin University, 2011)
This thesis presents an experimental study on the effect of a heated plume within vented enclosures. The characteristics of a heated plume within enclosures are studied using controlled and systematic experiments, simulating the movement of heated air due to the development of fire within a room.A short enclosure (Case CS1) and a tall enclosure (Case CS2) were subjected to two heating configurations representing natural and forced convection heat transfer. The cross-sectional dimension of the enclosures, and the heating power were maintained the same for both cases in order to compare the plume effects due to the change of height. For each case, different combinations of top ventilation were also considered for the present experiments.The air temperature and pressure within the enclosure were measured with suitable thermocouples and pressure probes, specially fabricated and mounted on racks that were positioned at three locations: (i) at 100 mm above the base of the enclosure; (ii) middle of the enclosure; and (iii) at 100 mm below the ceiling of the enclosure. The ceiling temperature profile was also obtained to determine the ceiling jet impingement.The experimental results show that for both case studies – CS1 and CS2, for the same heat transfer mechanism (natural or forced convection), the hot air temperature within the enclosure is decreased due to an increase in the number and size of vents. Hot air is exhausted quicker into the ambient and the exchange rate of hot air inside the enclosure and cool air from the ambient is increased. It was found that natural convection mechanism led to a higher ceiling and air temperature distribution than forced convection. The short enclosure had a higher ceiling temperature compared to the tall enclosure. Correlations for ceiling temperature distribution for short and tall enclosures are also provided. The study has resulted in obtaining valuable conclusions for the effect of a heated plume within a vented enclosure.